2005
DOI: 10.1007/s00438-004-1095-4
|View full text |Cite|
|
Sign up to set email alerts
|

Large deletions within the first intron in VRN-1 are associated with spring growth habit in barley and wheat

Abstract: The broad adaptability of wheat and barley is in part attributable to their flexible growth habit, in that spring forms have recurrently evolved from the ancestral winter growth habit. In diploid wheat and barley growth habit is determined by allelic variation at the VRN-1 and/or VRN-2 loci, whereas in the polyploid wheat species it is determined primarily by allelic variation at VRN-1. Dominant Vrn-A1 alleles for spring growth habit are frequently associated with mutations in the promoter region in diploid wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
729
2
17

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 590 publications
(791 citation statements)
references
References 42 publications
15
729
2
17
Order By: Relevance
“…TaGRP2 binding to the VRN1 pre-mRNA is required for the inhibition of VRN1 expression (21), so the disruption of this interaction can explain the earlier expression of VRN-D4. This mechanism is also consistent with the spring growth habit associated with large deletions in the first intron of VRN1, including the RIP-3 region (20,68).…”
Section: Vrn-d4 Provides Insights Into the Regulation Of Vernalizationsupporting
confidence: 81%
See 3 more Smart Citations
“…TaGRP2 binding to the VRN1 pre-mRNA is required for the inhibition of VRN1 expression (21), so the disruption of this interaction can explain the earlier expression of VRN-D4. This mechanism is also consistent with the spring growth habit associated with large deletions in the first intron of VRN1, including the RIP-3 region (20,68).…”
Section: Vrn-d4 Provides Insights Into the Regulation Of Vernalizationsupporting
confidence: 81%
“…None of the polymorphisms previously known to be associated with spring growth habit in VRN1 regulatory regions (17)(18)(19)(20) were found in VRN-D4. Therefore, alternative mechanisms are required to explain the dominant spring growth habit associated with the Vrn-D4 allele.…”
Section: Vrn-d4 Provides Insights Into the Regulation Of Vernalizationmentioning
confidence: 82%
See 2 more Smart Citations
“…This is not consistent with the suggestion that derepression of HvVRT2 is required for cold induction of HvVRN1. Another mechanism proposed to account for induction of HvVRN1 by cold involves the HvVRN2 floral repressor locus (Yan et al, 2004;Fu et al, 2005). We found that HvVRN1 is induced by cold in the spring barley Golden Promise, which lacks HvVRN2, suggesting that cold induction of HvVRN1 can occur independently of HvVRN2.…”
Section: Discussionmentioning
confidence: 69%